The paradoxes of communal friendship in Aristotle and the Stoics - Zamora Calvo, José María (Estudios de Filosofía, 2008)
From the long list of comments that have been written on the theory of friendship in Aristotle and, more specifically, in the Stoics, we are going to focus on the analysis of an ambiguity, producing paradoxes, which is inserted in the essence same of friendship. The aporia is mentioned by Aristotle himself, and contains some features that are fully current and new in the context of our societies: can you be a friend of a foreigner, a barbarian, someone who is not part of our community ?; Can there be cross-community friendships, or does the friendship require a new type of community, which transgresses the already established and consolidated communities? From the Stoic theory of friendship, which breaks the limits of the polis, the conception of a universal society that brings together the human race is an immense brotherhood founded on reason. [Fragment]